2013
DOI: 10.1111/tpj.12327
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of a TIRNBLRR locus from the wild North American grapevine species Muscadinia rotundifolia identifies paralogous genes conferring resistance to major fungal and oomycete pathogens in cultivated grapevine

Abstract: SUMMARYThe most economically important diseases of grapevine cultivation worldwide are caused by the fungal pathogen powdery mildew (Erysiphe necator syn. Uncinula necator) and the oomycete pathogen downy mildew (Plasmopara viticola). Currently, grapegrowers rely heavily on the use of agrochemicals to minimize the potentially devastating impact of these pathogens on grape yield and quality. The wild North American grapevine species Muscadinia rotundifolia was recognized as early as 1889 to be resistant to both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
166
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(172 citation statements)
references
References 63 publications
(82 reference statements)
6
166
0
Order By: Relevance
“…A small number of candidate effector genes from P. viticola have previously been reported [19], but these were identified in a cDNA library constructed from in vitro germinated zoospores, rather than from P. viticola during the infection process. Furthermore, with the recent cloning of first grapevine downy mildew resistance gene MrRPV1 [2], there is particular interest in trying to identify the Avr effector(s) secreted by P. viticola that initiate the ETI response mediated by MrRPV1. With the advent of highly sensitive nextgeneration sequencing technologies it is now possible to characterize the secretome of a biotrophic pathogen by transcriptome sequencing of infected plant tissues, followed by in silico removal of the host transcripts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small number of candidate effector genes from P. viticola have previously been reported [19], but these were identified in a cDNA library constructed from in vitro germinated zoospores, rather than from P. viticola during the infection process. Furthermore, with the recent cloning of first grapevine downy mildew resistance gene MrRPV1 [2], there is particular interest in trying to identify the Avr effector(s) secreted by P. viticola that initiate the ETI response mediated by MrRPV1. With the advent of highly sensitive nextgeneration sequencing technologies it is now possible to characterize the secretome of a biotrophic pathogen by transcriptome sequencing of infected plant tissues, followed by in silico removal of the host transcripts.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated applications of fungicides are currently the most effective method of protection, but this is costly for grapegrowers and is potentially harmful to the environment. The introduction of resistance (R) genes from wild grape species into susceptible V. vinifera cultivars would be of significant economic and environmental benefit [2]. However, the diversity and evolutionary potential of the pathogen populations pose a challenge to breeding strategies for durable resistance.…”
Section: Introductionmentioning
confidence: 99%
“…MrRUN1 and MrRPV1 are the first resistance genes (against powdery and downy mildew, respectively) from the grapevine to be cloned and functionally characterised. Feechan et al (2013) have shown that these resistance genes can be transferred from a wild grapevine species to premium V. vinifera varieties through genetic modification, and confer strong resistance against the two major pathogens of cultivated grapevines worldwide. The high level of synteny between the wild North American species Muscadinia rotundifolia and the European cultivated grapevine at the MrRUN1/MrRPV1 locus also opens up the possibility of obtaining resistant phenotypes from elite varieties using targeted genome engineering.…”
Section: Outlook For the Future Of Resistant Varietiesmentioning
confidence: 99%
“…This type of resistance is related to the detection of pathogen effectors by the plant due to specific resistance genes (R genes) [25,26]. Different loci have been found in several species of the Vitaceae family which confer resistance to E. necator; carrying resistance gene analogues (RGA) and in some cases associated to complete resistance to powdery mildew mostly related with PCD induction [27]. However, very few candidate R-genes have been identified to date and molecular defence mechanisms triggered by these resistance loci are being studied.…”
Section: Grapevine Defences Against E Necatormentioning
confidence: 99%
“…According to the closest SSR markers VMC4f3.1 and VMC8g9, this locus was mapped to a region in chromosome 12 and co-segregates with the Plasmopara viticola resistance locus Rpv1 [14,26,43,44]. The MrRUN1 and MrRPV1 genes, which code for TIR-NBS-LRR proteins (a class of R proteins), are the first cloned and functionally characterized resistance genes from grapevine [27]. The Ren1 locus, on the other hand, belongs to the V. vinifera cvs.…”
Section: Genetic Improvementmentioning
confidence: 99%